Soil characteristics for earthing of electric supply systems : with special reference to the area covered by the Cape Western Undertaking of the Electricity Supply Commission - Richter, A. N.(Alexander Nevil) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1956.